2009
DOI: 10.1097/yct.0b013e31817c73c3
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High Initial Seizure Threshold in a Catatonic Patient Treated With Electroconvulsive Therapy

Abstract: Because reports on exceptionally high initial seizure thresholds in ECT are rare, no definite conclusions can be drawn regarding its possible risk factors and management. However, since high initial seizure thresholds can complicate ECT, it is clinically important to further investigate this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As elderly depressed patients are at higher risk of serious medical comorbidity, including cardiovascular diseases [42], this clinical factor may contribute to the higher chance of increased seizure thresholds in older patients. Furthermore, such comorbidity often leads to pharmacotherapeutic treatments of which several are known to increase the seizure threshold, in particular anticonvulsants, benzodiazepines, beta-blockers, and calcium antagonists [55]. Although in most studies on the relation of seizure threshold and age the use of psychopharmacological drugs was an exclusion criterion, concomitant use of nonpsychotropic drugs was hardly mentioned.…”
Section: Clinical Factors and Increased Seizure Thresholdmentioning
confidence: 99%
“…As elderly depressed patients are at higher risk of serious medical comorbidity, including cardiovascular diseases [42], this clinical factor may contribute to the higher chance of increased seizure thresholds in older patients. Furthermore, such comorbidity often leads to pharmacotherapeutic treatments of which several are known to increase the seizure threshold, in particular anticonvulsants, benzodiazepines, beta-blockers, and calcium antagonists [55]. Although in most studies on the relation of seizure threshold and age the use of psychopharmacological drugs was an exclusion criterion, concomitant use of nonpsychotropic drugs was hardly mentioned.…”
Section: Clinical Factors and Increased Seizure Thresholdmentioning
confidence: 99%
“…One of the important points that is important in the treatment process with ECT is a generalized seizure that is caused by the device (tonic and colonic) in the patient. In this episode, a seizure has therapeutic properties that at least 20 seconds [15] can be seen as seizures in the electroencephalogram as visible seizures or 35 seconds [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these effects, sodium thiopental may cause tachycardia, hypotension, anaphylaxis, facial edema, myocardial depression, and some other side effects [30]. Some studies have shown that propofol and thiopental can reduce the duration of seizures [5,31], but propofol is more likely to reduce the duration of seizures compared with thiopental [16,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%